2006
DOI: 10.1161/01.atv.0000193625.32499.71
|View full text |Cite
|
Sign up to set email alerts
|

Role of Blood Cell–Associated AT1 Receptors in the Microvascular Responses to Hypercholesterolemia

Abstract: Objective-Hypercholesterolemia elicits a proinflammatory and prothrombogenic phenotype in the microvasculature that is characterized by activation and adhesion of blood cells. The angiotensin II receptor-1 antagonist Losartan prevents the induction of these responses. The objective of this study was to determine the relative contributions of blood cell-associated versus endothelium-associated AT1a-R to these hypercholesterolemia-induced microvascular alterations. Methods and Results-Leukocyte adhesion and emig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…Based on a study in the aorta of hyperlipidemic rabbits where AT1-R blockade abrogated vascular superoxide generation from NADH oxidase [9], and previous findings in our model that AT1-R activation mediates the leukocyte adhesion and oxidative stress in postcapillary venules [36] it is conceivable that the vascular and perhaps leukocyte NAD(P)H oxidase is activated through an AT1-R receptor-dependent pathway. Although platelet superoxide release can be stimulated by angiotensin II acting though AT1-R activation [37], platelet AT1-R does not appear to participate in the thrombogenic responses in our model [38]. Consequently, the activation of platelet NAD(P)H oxidase may involve an alternative pathway such as CD40L [39], which has also been implicated in hypercholesterolemia-induced inflammation [40,41].…”
Section: Discussionmentioning
confidence: 78%
“…Based on a study in the aorta of hyperlipidemic rabbits where AT1-R blockade abrogated vascular superoxide generation from NADH oxidase [9], and previous findings in our model that AT1-R activation mediates the leukocyte adhesion and oxidative stress in postcapillary venules [36] it is conceivable that the vascular and perhaps leukocyte NAD(P)H oxidase is activated through an AT1-R receptor-dependent pathway. Although platelet superoxide release can be stimulated by angiotensin II acting though AT1-R activation [37], platelet AT1-R does not appear to participate in the thrombogenic responses in our model [38]. Consequently, the activation of platelet NAD(P)H oxidase may involve an alternative pathway such as CD40L [39], which has also been implicated in hypercholesterolemia-induced inflammation [40,41].…”
Section: Discussionmentioning
confidence: 78%
“…Angiotensin-dependent inflammatory mechanisms have also been implicated in hypercholesterolemia-associated inflammation (38,39) and small, but increased plasma levels of cholesterol have been found in both postmenopausal women and ovariectomized rats. First, it is noteworthy that the levels of plasma cholesterol are in the normal range for healthy postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…We further tried to define the specific cell populations responsible for the mechanical injury-induced leukocyte recruitment and its blockade by olmesartan. Despite its importance in the vascular wall, the oxidative stress in circulating MNCs had not been carefully studied until recent observation of the microvasculature of hypercholesterolemic mice, 12 in which the importance of the Ang II type 1 receptor on leukocytes was addressed for the first time. Indeed, although MNCs from injured mice exhibited significant adhesion to the recipient injured artery, MNCs taken from mice without wire injury failed to adhere to the injured artery ( Figures 4B and 4C), suggesting a dominant role of MNCs in leukocyte recruitment to the femoral artery after injury.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The anti-inflammatory effect of ARB has been demonstrated in the microvasculature of the same mouse model. 11 Later, Petnehazy et al 12 reported that, in the atherosclerosis model, the leukocyte-associated but not vasculature-associated Ang II signal plays a dominant role in leukocyte recruitment in the microvasculature, indicating a previously unrecognized role of Ang II-dependent oxidative stress in leukocytes during atherosclerosis. In contrast, limited information is available regarding the role of leukocytes in their recruitment to the mechanically injured artery in vivo.…”
mentioning
confidence: 99%